The impact of picking success on customer purchasing behavior: an example of a Portuguese omni-channel retailer - Iziraren, Ilias (2019)
Problem definition: Supermarkets and grocery stores in developed economies are discovering the internet as a new marketplace via online deliveries. This study reveals the consequences of a low picking success (ratio of ordered to received items) and discusses the magnitude of the product unavailability. The picking success is thereby solely related to the operational performance (i.e. the ability of the seller of delivering the desired items). Academic / practical relevance: A broad product range and thin margins characterize today’s business environment for supermarkets and online retailers; by closely examining on how a poor picking success influences the customers purchasing behavior, important insights are gained regarding the relationship of the online delivery of goods and the respective customer satisfaction and ultimately retention. Methodology: A dataset consisting of 497,309 order shipments with in total 14,283,175 ordered products has been received through the collaboration with a large Portuguese omni-channel retailer. To establish relationships, causal analyses are used on matched pairs of customers. Thereby, a set of possible explanatory variables is analyzed (such as received discounts, remaining days to delivery etc.) to identify interrelations between the variables and the customer behavior after receiving a delivery with a low picking success. Results: By analyzing the data it becomes evident that a low picking success leads not only to a lower number of items per shipment afterwards, but also to a lower total number of purchases. Furthermore, customers are thereupon switching to lower-priced product alternatives, anticipating the scarcity of more expensive brand products, which might lead to even lower margins. This study also shows, how discounts can be used in order to (partly) compensate for a low picking success. Managerial implications: Most importantly, a low picking success has to be avoided to sustainably retain customers. In the short-term, a low picking success could be compensated through intelligent discounts – this is however not a sustainable method to avoid other side effects of a low picking success (which might be amongst others a deterioration in the reputation, a lower perceived brand value or product substitutions).